Exponentiated generalized exponential Dagum distribution - Nasiru, Suleman; Mwita, Peter N.; Ngesa, Oscar (Elsevier, 2017)
In this study, the exponentiated generalized exponential Dagum distribution has been proposed and studied. This family of distribution consists of a number of sub-models such as the exponentiated generalized Dagum distribution, Dagum distribution, Fisk distribution, Burr III distribution and exponentiated generalized exponential Burr III distribution among others. Statistical properties of the new family were also derived. Maximum likelihood estimators of the parameters of the distribution were developed and simulation studies performed to assess the properties of the estimators. Applications of the model was demonstrated to show its usefulness.
Keywords: Dagum distribution